Sharing inwardness in Teju Cole's Blind Spot. Issue 2 (2nd April 2020) - Gehlawat, Monika
ABSTRACT: This article argues that Teju Cole's recent book Blind Spot (2017) promotes the value of inwardness through its juxtaposition of photography and prose passages. Using Stephen Toulmin's theory of inwardness as an intentional state of contemplation, reflection, memory, and imagination, it studies how Cole's largely figureless photography and allusive prose assert an aesthetic of reticence intended to be shared as an alternative to the contemporary image realm of pervasive facial recognition. Contesting the careless, distracted consumption of figures and faces that pervades digital media, Cole uses the juxtaposition of prose and photography to offer a vision of what it might look like to look within, thereby advancing the practice of self-reflection as a form of intersubjective support. Blind Spot shares inwardness as an ethos of discretion, which also produces forms of empathy and curiosity, offering a visual account for how the enrichment of inward experience can actually serve to stimulate interpersonal bonds of solidarity. Using photography theory, and specifically reading the work of Michael Fried, Roland Barthes, Susan Sontag, and others, this article is one of the first academic accounts of Cole's singularity as a post-millennial writer and photographer, whose interdisciplinary work is deeply engaged in contemporary political and aesthetic concerns.